Association between varicocele grade and semen analysis parameter (Medical Journal of Indonesia, 2017)
Background: Varicocele is a condition characterized by elongation, dilatation and tortuousity of spermatic vein in pampiniform plexus. Approximately 50% of infertility cases among men are caused by varicocele. The varicocele may affect the components of sperm. This study aimed to determine the association between varicocele grade based on ultrasound Doppler examination and sperm concentration, sperm motility, and sperm morphology based on semen analysis examination. Methods: This was a descriptive, cross-sectional study which used secondary data from 85 patients that visited Department of Urology, Cipto Mangunkusumo Hospital, then underwent ultrasonography examination at Department of Radiology, Cipto Mangunkusumo Hospital and semen analysis examination at Department of Obstetrics and Gynecology, Cipto Mangunkusumo General Hospital. Results: Varicocele grade was significantly associated with sperm morphology, concentration and motility (all p<0.05). Significant association was found between maximum condition and semen analysis component. Conclusion: Varicocele grade may affect semen analysis component.